An improved process scan strategy to obtain high-performance fatigue properties for Scalmalloy®. (December 2022) - Schimbäck, D.; Mair, P.; Kaserer, L.; Perfler, L.; Palm, F.; Leichtfried, G.; Pogatscher, S.
Graphical abstract: Highlights: An improved scan strategy to avoid the interaction of the laser with the welding plume was applied. The impact of the laser energy on the welding mode and the burn-off of volatile elements was elaborated. Two different welding modes were used to evaluate the impact on the fatigue properties of Scalmalloy®. A fatigue strength of 360 MPa at 3 · 10 7 cycles ( R = 0.1 ) could have been achieved, outperforming conventionally and additively manufactured counterparts. Abstract: The choice of appropriate processing parameters in laser powder bed fusion is firmly established in the state-of-the-art additive manufacturing community. However, optimisation of scanning strategy would result in improved material properties. Here, the optimal scanning strategy for fatigue-loaded high-performance aluminium alloys, such as Scalmalloy®, was investigated. This study demonstrates how to reduce uncontrolled interactions of the laser with the distinct weld plume, created by highly volatile alloying elements such as Mg. Tensile and fatigue testing were used to assess the structural integrity of specimens, in which different welding modes had been used. It is shown that a combination of: scan vector angle restriction; reduction of the scan vector length; and laser spot adjustments reduce the overall defect size and improves the build quality in Scalmalloy®. A bimodal microstructure with outstanding mechanical properties was observed: an ultimate tensile strength of 524 MPa was achieved with 17 % elongation at fracture. In order to evaluate the influence of the defect size, fatigue tests were performed at a stress ratio of R = 0.1 . Under optimal processing conditions, fatigue strengths of up to 360 M P a at 3 · 10 7 cycles were obtained, significantly outperforming both conventionally and additively produced aluminium alloys.